Efficacy and safety of the herbal formula Naesohwajung-tang for functional dyspepsia: a randomized, double-blind, placebo-controlled, multi-center trial - Ha, Na-Yeon; Ko, Seok-Jae; Park, Jae-Woo; Kim, Jinsung (Frontiers in Pharmacology, 2023)
Background: Current treatment and management options for functional dyspepsia (FD) often fail to alleviate symptoms. Naesohwajung-tang (NHT) is a herbal formula frequently used to treat functional dyspepsia in traditional Korean medicine. However, few animal and case reports on the use of Naesohwajung-tang for functional dyspepsia treatment exist, and the clinical evidence remains deficient. Objectives: This study aimed to evaluate the efficacy of Naesohwajung-tang in patients with functional dyspepsia. Methods: We enrolled 116 patients with functional dyspepsia at two study sites in this 4 weeks, randomized, double-blind, placebo-controlled trial and randomly assigned them to either the Naesohwajung-tang or placebo group. To evaluate the efficacy of Naesohwajung-tang, the primary endpoint was a score on the total dyspepsia symptom (TDS) scale after treatment. The overall treatment effect (OTE), single dyspepsia symptom (SDS) scale, food retention questionnaire (FRQ), Damum questionnaire (DQ), functional dyspepsia-related quality of life (FD-QoL) questionnaire, and gastric myoelectrical activity measured using electrogastrography were evaluated as secondary outcomes. Laboratory tests were performed to confirm the safety of the intervention. Results: The 4 weeks administration of Naesohwajung-tang granules demonstrated a significantly higher reduction in the total dyspepsia symptom (p < 0.05) and a higher degree of improvement in the total dyspepsia symptom (p < 0.01) than the placebo group. Patients who underwent Naesohwajung-tang had a significantly higher overall treatment effect and a greater increase in the degree of improvement in scores such as epigastric burning, postprandial fullness, early satiation, functional dyspepsia-related quality of life, and Damum questionnaire (p < 0.05). Additionally, the Naesohwajung-tang group showed a greater effect in preventing a decrease in the percentage of normal gastric slow waves after meals than the placebo group. As a result of subgroup analyses using the degree of improvement in total dyspepsia symptom, Naesohwajung-tang was found to be more effective than placebo in female, younger patients (<65 years), with a high body-mass index (≥22), overlap type, food retention type, and Dampness and heat in the spleen and stomach systems pattern. There was no significant difference in the incidence of adverse events between the two groups. Conclusion: This is the first randomized clinical trial to verify that Naesohwajung-tang leads on symptom relief in patients with functional dyspepsia. Clinical Trial Registration:https://cris.nih.go.kr/cris/search/detailSearch.do/17613, identifier KCT0003405